ANALISIS HUBUNGAN JUMLAH KECELAKAAN TERHADAP TINGKAT FATALITAS LALU LINTAS DI RUAS JALAN SUDIRMAN KOTA MAUMERE - Kabupung, Alfrendo; Chandra, Jimmy; Duran, Yohanes Gualbertus G. Lesu (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Traffic accidents remain a major issue affecting public safety worldwide. This study aims to analyze the relationship between the number of traffic accidents and the level of fatality on Sudirman Road in Maumere City. The research uses secondary data from the Sikka District Police covering the period 2019–2023, along with primary data from traffic volume surveys conducted in the study area. The analytical methods used include simple linear regression and correlation to determine the strength and direction of the relationship between the variables. The results show a fairly strong positive linear relationship between the number of accidents and the level of fatality, with a coefficient of determination (R²) of 0.6722. This means that approximately 67.22% of the variation in fatality levels can be explained by changes in the number of accidents. These findings indicate that an increase in the number of accidents is likely to be followed by a higher fatality rate. This research is expected to serve as a reference for improving traffic safety measures in urban areas. Keyword: traffic accidents, fatality rate, linear regression, Jalan Sudirman, Maumere